Economic crisis in South Africa: 1974-1986 - Gelb, Stephen (My University, 1987)
Symptoms of economic crisis - long run economic decline – are now so widespread in South Africa that the existence of such a crisis is increasingly taken for granted in public discussions of the state of the economy and its possible improvement. Even the Governor of the Reserve Bank, Dr Gerhard de Kock, now uses the "structural slowdown" (his label for economic crisis) to fend off the charge that the primary responsibility for economic decline, culminating in the foreign debt debacle of August 1985, lies with the Banks' shift, in the years from 1979, to a fundamentally different policy orientation. He has recently argued that "the structural slowdown of South Africa's real rate of growth began roundabout 1974 and not in 1981." The drop from an annual average growth rate of real GDP of 4,9% (1940 - 1974) to 1,9% (1974 -1985) was, he argued, "mainly the result of a decline in the ratio of exports to Gross Domestic Product and a weakening of the terms of trade ... [These and other] unfavourable exogenous developments since the early seventies made drastic and painful adjustments in South Africa unavoidable." (1)
African Studies Seminar series. Paper presented August, 1987
Keywords: Saving and investment. South Africa; Recessions. South Africa; South Africa. Economic conditions. 1961-1991